Academic stress and stress coping style in nursing undergraduates: Predictors of academic performance in a public tertiary institution in Nigeria - Yahaya Jafaru; Esther Kikelomo Afolabi (Tabriz University of Medical Sciences, 2023)
Background: The students' ability to withstand the effect of stress is significantly determined by their coping ability. Their inability to cope effectively with stress may lead to low academic performance. This study aimed to investigate academic pressure and coping style as predictors of the academic performance of nursing undergraduates. Methods: This study adopted a cross-sectional descriptive research design. The target population was nursing undergraduates at the Federal University of Birnin-Kebbi. A sample size of 118 was selected as respondents. Data were collected and analyzed using Statistical Package for the Social Science (SPSS) version 26. Frequencies and percentages, Pearson product moment correlation, and multiple linear regression were used in data analysis. Results: The respondents' mean age was 25.09 (SD=4.53). Females were 55.9%. There was a weak negative correlation between cumulative grade point average (CGPA) and mean academic stress (AS) (r=-0.141, P=0.065), a weak positive correlation between CGPA and mean stress coping style (SCS) (r=0.237, P=0.005), and a weak positive correlation between mean AS and mean SCS was 0.008 (P=0.466). Mean AS was not a significant predictor of academic performance t (115)=-1.589, P=0.115. Mean SCS was a significant predictor of academic performance t (115)=2.656, P=0.009. Conclusion: The mean AS was not a significant predictor of academic performance. However, the mean SCS was a significant predictor of academic performance with a positive and significant correlation.